Correlation Analysis of the Logistic Performance Index (LPI) and Environmental Quality in Asia-Pacific Countries, 2010–2022 - Sinaga, Agus Suhery; Soetjipto, Widyono (Journal Research of Social Science, Economics, and Management, 2026)
Improvements in logistics facilities and infrastructure have increased the volume of world trade transportation. On the other hand, increased trade transportation activities may have the potential to reduce environmental quality through emissions. Therefore, this study analyzes the relationship between logistics performance and environmental quality, which is approached by using the ecological footprint. Using a quantitative approach, this study employs panel data regression with a fixed effect model on data from 17 APEC member economies over the period 2010–2022. A robustness check is also conducted using quantile regression to evaluate the consistency of results across different data distribution quartiles.. The results of panel data regression with fixed effect model show that Logistic Performance Index (LPI) has a positive and significant effect on ecological footprint. These findings have important implications for sustainable development policy. Efforts to reduce environmental impact should focus on improving logistics performance in a sustainable manner that mitigates its impact to environmentally unfriendly economic growth.